2006
DOI: 10.1007/s10682-006-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing increases infection success in the holoparasitic mistletoe Tristerix aphyllus (Loranthaceae)

Abstract: Most studies on the fitness advantage of outbreeding in host-parasite systems have been assessed from the host rather than the parasite perspective. Here, we performed experimental pollination treatments to evaluate the consequences of outbreeding on fitness-related traits in the holoparasitic mistletoe Tristerix aphyllus in a 2-year field study. Results indicate that self-pollinated plants had a lower fruit production than outcrossed plants (20.4% and 29.5% reduction in 2002 and 2003, respectively), and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…However, the effects of host species on the growth of R. alectorolophus were not influenced by pollination type, suggesting that inbreeding did not influence the ability of the parasites to overcome specific resistance mechanisms. In contrast, in the holoparasite Tristerix aphylla, which grows endophytically in South American cacti, inbreeding reduced many early fitness traits, including infection success (Gonz ales et al, 2007). It has been suggested that outbreeding is especially important for parasites, because they have to overcome defences evolving in different host genotypes (Agrawal and Lively, 2001;Gonz ales et al, 2007).…”
Section: Population Differences In Host Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effects of host species on the growth of R. alectorolophus were not influenced by pollination type, suggesting that inbreeding did not influence the ability of the parasites to overcome specific resistance mechanisms. In contrast, in the holoparasite Tristerix aphylla, which grows endophytically in South American cacti, inbreeding reduced many early fitness traits, including infection success (Gonz ales et al, 2007). It has been suggested that outbreeding is especially important for parasites, because they have to overcome defences evolving in different host genotypes (Agrawal and Lively, 2001;Gonz ales et al, 2007).…”
Section: Population Differences In Host Qualitymentioning
confidence: 99%
“…In contrast, in the holoparasite Tristerix aphylla, which grows endophytically in South American cacti, inbreeding reduced many early fitness traits, including infection success (Gonz ales et al, 2007). It has been suggested that outbreeding is especially important for parasites, because they have to overcome defences evolving in different host genotypes (Agrawal and Lively, 2001;Gonz ales et al, 2007). However, little is known about the genetics of host-parasite coevolution in Rhinanthus.…”
Section: Population Differences In Host Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Some eff ort has been dedicated to the Ligaria and Tristerix in the temperate regions of Argentina (Galetto et al 1990;Rivera et al 1996;Tadey & Aizen 2001;Aizen & Harder 2007) and in the semiarid region of Chile (Gonzáles et al 2007). Gonzáles et al (2007) demonstrated that outcrossing could increase the percentage of germination in T. aphyllus, which had never been shown before in mistletoes. Studies of other neotropical mistletoe genera do not off er the same degree of complexity.…”
Section: Mistletoe Pollination and Seed Dispersalmentioning
confidence: 99%